A Method of the Durability Life Prediction for Chinese Historical Reinforced Concrete Structure. Issue 2 (April 2021) - Jin, Hui; Chun, Qing
Abstract: In order to evaluate the durability of historical reinforced concrete buildings with square rebars more accurately, a calculation method of durability life for this type of buildings is proposed in this paper. The method mainly includes structural component importance analysis and the calculation method of the durability life prediction for single concrete component with square rebars. Compared with the existing durability evaluation standards and methods based on round rebars, this method is closer to the actual structure status. The works of the paper can be used for the durability evaluation of square steel reinforced concrete buildings and provide a reference for its repair and protection.